El camino del notario infernal de México a Kuks - Štěpánek, Pavel (Theatrum historiae, 2012)
The way of the infernal notary from Mexico to Kuks is a study about the penetration of a Mexican myth in the baroque Bohemia. It deals with the theatre person of the notary (notarius) Ficli-pucli who appears in a celebration occurred at the court of the Count Sporck in his residence at Kuks, a bath and cultural centre founded by himself. The analysis of the word proves that derivates from the name of the Mexican deity Huitzilopochtli, one of the most important of the Aztec Pantheon. The recompilation of prints and graphics demonstrates that it comes though many books that inform about the overseas (Aztec) religions. The tradition continues till the end of the 19th century, as we can see by the mutilated expressions of that name in the poetry (documented in Beethoven and, after all, Heine) and even in the Bohemian Glass.